Hi friends,
Given the formula to calculate the future value of a current amount, and rearranging the formula to calculate t, the number of periods, such that:
FV = PV(1+i)^t
FV/PV = (1+i)^t
Taking loge of both sides gives: loge(FV/PV) = loge(1+i)^t
Hence by one of the logarithmic laws: loge(FV/PV) = t*loge(1+i)
Thus: t = loge(FV/PV)/loge(1+i)
Why is it that we cannot cancel the two log of base e here and simplify down to t = (FV/PV) / (1+i)?
Both gives different answers and I'm just wondering why you cannot cancel or simplify out the loge?
Thanks.
Given the formula to calculate the future value of a current amount, and rearranging the formula to calculate t, the number of periods, such that:
FV = PV(1+i)^t
FV/PV = (1+i)^t
Taking loge of both sides gives: loge(FV/PV) = loge(1+i)^t
Hence by one of the logarithmic laws: loge(FV/PV) = t*loge(1+i)
Thus: t = loge(FV/PV)/loge(1+i)
Why is it that we cannot cancel the two log of base e here and simplify down to t = (FV/PV) / (1+i)?
Both gives different answers and I'm just wondering why you cannot cancel or simplify out the loge?
Thanks.